Mechanosensing through focal adhesion‐anchored intermediate filaments. Issue 2 (17th December 2013) - Gregor, Martin; Osmanagic‐Myers, Selma; Burgstaller, Gerald; Wolfram, Michael; Fischer, Irmgard; Walko, Gernot; Resch, Guenter P.; Jörgl, Almut; Herrmann, Harald; Wiche, Gerhard
Abstract : Integrin‐based mechanotransduction involves a complex focal adhesion (FA)‐associated machinery that is able to detect and respond to forces exerted either through components of the extracellular matrix or the intracellular contractile actomyosin network. Here, we show a hitherto unrecognized regulatory role of vimentin intermediate filaments (IFs) in this process. By studying fibroblasts in which vimentin IFs were decoupled from FAs, either because of vimentin deficiency (V0) or loss of vimentin network anchorage due to deficiency in the cytolinker protein plectin (P0), we demonstrate attenuated activation of the major mechanosensor molecule FAK and its downstream targets Src, ERK1/2, and p38, as well as an up‐regulation of the compensatory feedback loop acting on RhoA and myosin light chain. In line with these findings, we show strongly reduced FA turnover rates in P0 fibroblasts combined with impaired directional migration, formation of protrusions, and up‐regulation of "stretched" high‐affinity integrin complexes. By exploiting tension‐independent conditions, we were able to mechanistically link these defects to diminished cytoskeletal tension in both P0 and V0 cells. Our data provide important new insights into molecular mechanisms underlying cytoskeleton‐regulated mechanosensing, a feature that is fundamental for controlled cell movement and tumor progression.—Gregor, M., Osmanagic‐Myers, S., Burgstaller, G., Wolfram, M., Fischer, I., Walko, G., Resch, G. P., Jörgl, A., Herrmann, H., Wiche, G. Mechanosensing through focal adhesion‐anchored intermediate filaments. FASEB J. 28, 715–729 (2014). www.fasebj.org